1967
DOI: 10.1002/pol.1967.150050407
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the γ‐radiation‐induced polymerization of methyl methacrylate in the solid state

Abstract: SynOPhStudies have been made of the y-radiation-induced polymerization of methyl methacrylate in bulk, in the solid state a t a temperature of -65°C. and a radiation intensity of 346,000 rad/hr. The reaction was found to have an extremely long induction period (-50 hr.) when pure monomer was used, and to be firsborder with respect to polymer concentration. This firsborder dependency was confirmed by a series of irradiations in which 0.6% poly(methy1 methacrylate) was dissolved in the monomer before irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1969
1969
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…They suggested that self-acceleration of the polymerization reaction was taking place, which was evidenced by the increasing yield of polymer with higher doses of radiation absorbed. A similar phenomenon was observed in the case of the polymerization of methyl methacrylate [230].…”
Section: Szalinska and Pietrzaksupporting
confidence: 71%
“…They suggested that self-acceleration of the polymerization reaction was taking place, which was evidenced by the increasing yield of polymer with higher doses of radiation absorbed. A similar phenomenon was observed in the case of the polymerization of methyl methacrylate [230].…”
Section: Szalinska and Pietrzaksupporting
confidence: 71%
“…Although topochemical radical polymerization gives highly stereoregular polymers, the scope of the stereospecific polymerization of vinyl compounds is exclusively limited to 1,3-diene monomers and could not be used for common vinyl monomers. For vinyl monomers, it is difficult to prepare well-organized crystals, but it is noteworthy that solid-state polymerization of MMA gave lower syndiotactic polymers than that in solution probably due to the confinement effect …”
Section: Stereospecific Radical Polymerizationmentioning
confidence: 99%
“…For vinyl monomers, it is difficult to prepare wellorganized crystals, but it is noteworthy that solid-state polymerization of MMA gave lower syndiotactic polymers than that in solution probably due to the confinement effect. 144…”
Section: Crystalline Solid-state Polymerizationmentioning
confidence: 99%
“…This monomer only leads to trace amounts of polymer when irradiated in the crystalline state (2). If, however, the monomer is subjected to very high doses of radiation, polymerization takes place after a long induction period (43). Here again the products of the radiolysis of the monomer presumably create imperfections in the crystal which favor the migration of monomer molecules towards the active sites.…”
Section: ) Influence Of the Accumulated Polymermentioning
confidence: 99%